2022
DOI: 10.1017/s1478951521001887
|View full text |Cite
|
Sign up to set email alerts
|

The burden in palliative care assistance: A comparison of psychosocial risks and burnout between inpatient hospice and home care services workers

Abstract: Objective Literature suggests that home care professionals could be at higher risk of burnout than their colleagues in hospital settings, but research on home-based palliative care is still limited. Our study investigates psychosocial risk factors and burnout among workers involved in palliative care, comparing inpatient hospice, and home care settings. Method A cross-sectional study was carried out in a single palliative care organization providing inpatient hospice-based and home care-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…According to PSC Benchmark Standards, the mean PSC value found in our study suggests a high-risk level ( Dollard and Bailey, 2019 ). Although none of these studies concerned the Italian context, making comparison difficult, it is noteworthy that the mean PSC score in our sample was also lower than those found in previous Italian studies among workers involved in palliative cares ( Fattori et al, 2022 ) and healthcare workers facing COVID-19 ( Fattori et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 84%
“…According to PSC Benchmark Standards, the mean PSC value found in our study suggests a high-risk level ( Dollard and Bailey, 2019 ). Although none of these studies concerned the Italian context, making comparison difficult, it is noteworthy that the mean PSC score in our sample was also lower than those found in previous Italian studies among workers involved in palliative cares ( Fattori et al, 2022 ) and healthcare workers facing COVID-19 ( Fattori et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 84%
“…There was one study that compared palliative healthcare professionals with other healthcare professionals: Yildrim et al [40] performed a comparison study between hematology, oncology, and palliative care nurses. The study of Diehl and colleagues made a comparison between different types of palliative nurses: those providing specialized palliative care compared with those providing general palliative care; Fattori et al [18] compared inpatient hospice and home care service workers.…”
Section: Resultsmentioning
confidence: 99%
“…There was strong evidence (five high-quality studies2 7 61 63 65) showing that factors such as change management and the overall organisational culture in a hospice are associated with poorer psychological well-being. For example, one study reported that how organisational change is managed and communicated in the organisation was a significant predictor of depression (n=91, beta=−2.684, p≤0.01) 66…”
Section: Resultsmentioning
confidence: 99%
“…There was insufficient evidence suggesting that hospice workers’ psychological well-being is affected by ‘work intrusiveness’, the extent to which their work intrudes into their private life 65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation